Ausstrahlung und Widerschein: Wahrnehmung und Wirkung der Wittenberger Universität im Europa des 16. Jahrhunderts - Beyer, Michael; Hauger, Martin; Leppin, Volker (Evangelische Verlagsanstalt, 2023)
[Impact and respectiveness. Perception and influence of Wittenberg University in 16th century Europe] For now more than 50 years, the Theologische Arbeitskreis für Reformationsgeschichtliche Forschung (TARF) has provided international Luther and Reformation research with a place for exchange between the major Luther Congresses. In doing so, primarily in Wittenberg, during the 1970s and 1980s it gave protection to the Wittenberg Luther House from ideological infiltration. In the same, it offered a chance for mutual exchange of Luther research between East and West respecting both, Church and theology. During the Reformation decade from 2008 to 2017 and later on, it pursued the plan to explore the European reception of Reformation stimuli radiating from Wittenberg, which would unfold specific effects under different historical circumstances at different places. This volume offers a selection of the contributions to this project.